The Skillset of an Effective Compliance Officer - Krambia-Kapardis, Maria (My University, 2019)
After briefly considering the major role corporate culture has to play in the field of compliance and ways of succeeding in that role, attention turns to the issue of the skills a compliance officer (CO) needs to possess in order to be effective. The chapter addresses the four strategies a CO will experience in carrying out his/her duties as well as the specific skillset the CO ought to possess in order to be effective. A discussion then follows on the importance of one’s personal values and behavior. Finally, it is emphasized that there is a limit on how much an effective CO can achieve in a company as it depends on the Board’s political will to provide the necessary resources to the compliance department.
Keywords: Effective compliance officer; Skillset; Commitment; Ethical behavior